Study on the stability of high and steep slopes under deep bench blasting vibration in open-pit mines - Su, Hengyu; Ma, Shu (Frontiers in Earth Science, 2022)
In order to study the stability of the high and steep slope of an open-pit mine under deep bench blasting vibration, a mine in Inner Mongolia is taken as the engineering background, and the mechanical parameters of rock samples were determined based on uniaxial and triaxial instruments. The stability of the high and steep slope of the open-pit mine under static and dynamic loads was analyzed by using field vibration monitoring and numerical simulation methods. The results show that the vibration range of the vibration wave is -1.25–1.25 cm/s, and the vibration wave shows a gradual attenuation trend. The Sadovsky regression equation was used to analyze and fit the monitoring data and the corresponding regression equations in each direction were obtained. Under static action, the safety factor of the high and steep slope is 1.20, and the displacement of the sliding zone passing through the slope is small, so the slope stability is good. Under the action of dynamic blasting load, the overall displacement of the slope is small, and the change of displacement decreases with the decrease of the vibration wave.